2007
DOI: 10.1357/002224007781567621
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of the use of sediment traps for estimating upper ocean particle fluxes

Abstract: This review provides an assessment of sediment trap accuracy issues by gathering data to address trap hydrodynamics, the problem of zooplankton "swimmers," and the solubilization of material after collection. For each topic, the problem is identified, its magnitude and causes reviewed using selected examples, and an update on methods to correct for the potential bias or minimize the problem using new technologies is presented. To minimize hydrodynamic biases due to flow over the trap mouth, the use of neutrall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
400
0
5

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 464 publications
(434 citation statements)
references
References 196 publications
9
400
0
5
Order By: Relevance
“…A review by Buesseler et al (2007) suggested that 234 Th-bearing particles were under-trapped by a factor of about 2 and suggested some processes that could be sources of trap error, such as undercollection of slow settling particles by hydrodynamic bias, particle solubilisation within the trap before sample processing, and "swimmer" related artefacts. Haskell et al (2013) reported that ST collected about r20% of the F Th,SW in two consecutive years and proposed that the main cause of this mismatch was the undertrapping of small, 234 Th-enriched slow sinking particles.…”
Section: Pigments and Poc In Sediment Trapsmentioning
confidence: 99%
“…A review by Buesseler et al (2007) suggested that 234 Th-bearing particles were under-trapped by a factor of about 2 and suggested some processes that could be sources of trap error, such as undercollection of slow settling particles by hydrodynamic bias, particle solubilisation within the trap before sample processing, and "swimmer" related artefacts. Haskell et al (2013) reported that ST collected about r20% of the F Th,SW in two consecutive years and proposed that the main cause of this mismatch was the undertrapping of small, 234 Th-enriched slow sinking particles.…”
Section: Pigments and Poc In Sediment Trapsmentioning
confidence: 99%
“…The particle interceptor traps were deployed below the base of Z eu (50 to 75 m) and below the surface mixed layer (6 to 26 m; Table 1), so the measured sinking fluxes represented the export of material sinking out of Z eu . Particle interceptor traps may collect material originating from different areas, so the interpretation of the location and time of origin of the collected particles could be biased (Buesseler et al 2007a). However, during the Lagrangian study (Days 2 to 6), the free-drifting particle interceptor trap array was deployed and drifted in close proximity to the Lagrangian drifting buoy deployed to track the water mass under investigation.…”
Section: Linking Particle Sinking Fluxes To Epipelagic Processesmentioning
confidence: 99%
“…Similar particle interceptor traps and mooring arrays have been used in other studies (Michel et al 2002, Caron et al 2004, and comparisons with flux estimates using 234 Th have shown close agreement in estimated carbon fluxes (Th-derived carbon flux = 0.68 + 1.05 drifting trap flux; n = 13, r 2 = 0.89, p < 0.001; Tremblay et al 2006). The average increase in DOC concentration within the particle interceptor traps during deployment intervals was 11 ± 6% below Z eu and 10 ± 5% at 150 m throughout the study period, reflecting the potential loss of particulate organic matter (POM) to the dissolved phase (solubilization; Buesseler et al 2007a) during trap deployments. Solubilization can result from the diffusion of dissolved organic matter from aggregates, bacterial degradation of POM, the activity of swimmers, and physical-chemical processes affecting the dissolution of POM (Buesseler et al 2007a).…”
Section: Linking Particle Sinking Fluxes To Epipelagic Processesmentioning
confidence: 99%
See 2 more Smart Citations